PENGARUH E-WOM KONTEN TIKTOK TERHADAP MINAT KUNJUNGAN DI SETU PATOK KABUPATEN CIREBON - Spika Yusmiyati; Abdul Khalim (Bajang Institute, 2025)
Setu Patok is a lake or reservoir whose construction began in 1921 and was completed in 1925 by the Dutch. It is located at the coordinates 6°47'04.9